A study of terminological neologisms popularized by the newspaper 'El País' and their inclusion in the dictionary - Cañete González, Paola; Fernández-Silva, Sabela; Villena Araya, Belén (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Social transformations and technological advances lead to the coining of new words, both in general and specialized languages, which are often disseminated to the general audience via the written press. This study is aimed at analyzing how subject-specific areas contribute to the enrichment of the Spanish lexicon. For that purpose, the neologisms of three sections of the Spanish newspaper El País between 2003 and 2013 were analyzed. The occurrence of terminological and non-terminological neologisms from different subject-fields was compared, and the inclusion of these lexical units in the Diccionario de la Lengua Española (RAE) was examined. Results showed a moderate dissemination of terminology through the press, differences between both types of neologisms with regard to the formation processes and their function in discourse. Finally, an important contribution of terminological neologisms to the dictionary was observed, therefore confirming the role of the press in the determinologization and dissemination of these units.
Keywords: neologism; terminological neologism; press; dictionary